Differential Metabolomic Responses of Kentucky Bluegrass Cultivars to Low Nitrogen Stress - Sun, Xiaoyang; Guo, Zhixin; Jiang, Yiwei; Qin, Ligang; Shi, Zhenjie; Dong, Lili; Xiong, Liangbing; Yuan, Runli; Deng, Wenjing; Wu, Hanfu; Liu, Qingqing; Xie, Fuchun; et al. (Frontiers in Plant Science, 2022)
Kentucky bluegrass (Poa pratensis L.) is a cool-season turfgrass that responds strongly to nitrogen (N), but the metabolomic responses of this species to N supply is unknown. The N-tolerant cultivar Bluemoon and N-sensitive cultivar Balin were exposed to normal N (15 mM) and low N (0.5 mM) for 21 days for identification of differentially expressed metabolites (DEMs) between normal N and low N treatments. Balin had more reductions of chlorophyll and total soluble protein concentrations and a higher accumulation of superoxide radicals under low N stress. A total of 99 known metabolites were identified including 22 amino acids and derivatives, 16 carbohydrates, 29 organic acids, and 32 other metabolites. In Bluemoon, β-alanine metabolism was most enriched, followed by alanine, aspartate, and glutamate metabolism, biosynthesis of valine, leucine, and isoleucine biosynthesis, and glycine, serine, and threonine metabolism. In Balin, alanine, aspartate and glutamate metabolism were most enriched, followed by the tricarboxylic acid (TCA), glyoxylate and decarbohydrate metabolism, and carbon fixation. Bluemoon generally maintained higher TCA cycle capacity and had more downregulated amino acids, while changes of more organic acids occurred in Balin under low N stress. Some metabolite changes by low-N stress were cultivar-specific. The results suggested that regulation of metabolites related to energy production or energy saving could contribute to low N tolerance in Kentucky bluegrass.